Impelementasi Kurikulum 2013 pada Mata Pelajaran Aqidah Akhlak Kelas V di MI Raudlatut Thalabah Kediri - M. Gholy Naimmummaskub; Wasito (PT. Pusmedia Group Indonesia, 2023)
This study aims to determine the implementation of the 2013 curriculum Aqidah Akhlak subject in the Madrasah Ibtidaiyah curriculum is one of the Islamic Religious Education subjects directed at preparing students to recognize, understand, believe, appreciate, and practice praiseworthy morals, which then become the basis for their outlook on life (way of life) through activities of guidance, teaching, practice, use of experience and habituation. Aqidah Akhlak learning in Madrasahs today is inseparable from the curriculum that has been set by the government, namely using the 2013 Curriculum. The Education Curriculum in Indonesia is always dynamic. The implementation of the 2013 Curriculum currently aims to prepare Indonesian people to have the ability to live as individuals and citizens who are faithful, productive, creative, innovative, and affective and able to contribute to the life of society, nation, state, and world civilization. The data collection method in this research uses three ways, namely: Interview method, observation method and documentation method. Qualitative data analysis is inductive where the analysis is based on the data obtained, then certain relationship patterns are developed. In the 2022/2023 academic year, 5th grade students of MI Raudlatut Thalabah have been introduced and have also practiced the learning process in accordance with the 2013 curriculum through a scientific approach with five learning steps, namely observing, questioning, collecting data, reasoning and communicating. Keywords: Implementation of 2013 Curriculum; Aqidah Akhlak Lesson.